(untitled) (Research, Society and Development, 2018)
This article aims to discuss the readers skills of college students. National performance assessment tests are analytical references. The undergraduation course institutions should turn their attention to promoting the students integral formation, developing reading skills and also writing in social practices. The remarkable cultural diversity manifested in the academic environment and litteracies practices can contribute to better use of education, more skills for work and active citizenship. It is a descriptive and exploratory research, with procedure, combined with the field study. As a data instrument, we used a questionnaire to draw a profile of the public, and applied, to fifty participants, a set of questions extracted from ENADE test. The discussion is expanded with theoretical contributions of Rojo (2004), Kleiman (2002), among others, in to reflect the importance of reading and their strategies.